Radio polarization measurements from RRAT J1819-1458 - Karastergiou, A; Hotan, A; Straten, W; McLaughlin, M; Ord, S (2009)
We present the first polarization measurements of the radio emission from RRAT J1819$-$1458. Our observations, conducted in parallel to regular timing sessions, have yielded a small number of bright and polarized pulses. The polarization characteristics and integrated profile resemble those of normal pulsars with average spin-down energy (Edot): moderate to low linear polarization in the integrated profile despite relatively high polarization in the individual pulses. On average, a small degree of circular polarization is also observed. The polarization position angle executes a remarkably smooth, steep S-shaped curve, interrupted by two orthogonal jumps. Based on the shape of the PA swing, we place some constraints on the emission geometry. We compare these polarization properties to those of other radio emitting neutron star populations, including young pulsars, pulsars with a high surface magnetic field and radio emitting magnetars. From the polarization measurements, the Faraday rotation measure of this RRAT is derived.